FORMULASI SHAMPO CAIR TRANSPARAN SARI BUAH JERUK NIPIS (Citrus aurantifolia S.) - Fauzia Ningrum Syaputri; Amran Ilyas Tandjung; Faradiba Faradiba (As-Syifaa Jurnal Farmasi, 2017)
The objective of this research was to determine a stable formula and determine the influence of carbopol enhancing in the preparation of lime extract (Citrus aurantifolia S.) transparent liquid shampoo (TLS). Shampoo made from TLS formulation lime extract in three different concentration of carbopol (0.5% : 0.6% : 0.7%). Shampoo were then characterized for stability test before and after accelerated storage include organoleptic test, the foam test, test the pH stability, viscosity measurements, and rheological. The result of organoleptic observation before and after accelerated storage, either formula with concentration of carbopol 0.5%, 0.6%, or 0.7%, did not show a change for the color, smell and consistency. There are no differences in foam test from TLS with shampoo preparations comparison. There are no change of PH test in TLS with concentration of carbopol 0.5%, 0.6%, or 0.7% before and after accelerated storage. There are no change of viscosity test in TLS with concentration of carbopol 0.5%, 0.6%, or 0.7% before and after accelerated storage. Third shampoo formula has plastic flow. Formulation of TLS with concentration of carbopol 0.5% have the most optimal stability than TLS with concentration of carbopol 0.6% and 0.7%.